Modified pEO-based solid-state electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202611193460.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]基于以上困境,亟需开发一种效果显著、制备高效的改性PEO基固态电解质,从根源上同时解决PEO的离子传导和界面稳定性问题
(1)本发明针对PEO基固态电解质的离子传输和高压界面稳定性的问题根源,采用特定填料进行阳离子化学环境调控,有机添加剂中的羧基可以削弱PEO对锂离子的强束缚作用,提高PEO的离子电导率;同时吸收高电压下PEO产生的氢质子,防止强酸性环境持续破坏电极/电解质界面,最终实现PEO基固态电解质离子电导率和高压界面稳定性的协同改善;
Smart Images

Figure CN122992166A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery technology, specifically relating to a modified PEO-based solid electrolyte, its preparation method, and its application. Background Technology
[0002] Polymer electrolytes have become the most commercially promising choice for all-solid-state lithium metal batteries due to their excellent interfacial contact, superior processability, and low cost. Polyethylene oxide (PEO) is a typical example that has achieved commercial application first. However, its less-than-ideal ionic conductivity and high voltage stability limit its further application in high-energy-density all-solid-state lithium metal batteries. The fundamental reason is the high ion transport barrier caused by the strong binding effect of PEO on lithium ions, resulting in low ionic conductivity (<10−4 S / cm) and low lithium-ion transference number (<0.2). Furthermore, the O–H and C–H bonds of PEO become unstable under high voltage, and the generated hydrogen ions readily combine with lithium salt anions to form strong acids. This strongly acidic environment continuously decomposes the electrode / electrolyte interface, leading to rapid battery degradation.
[0003] Researchers have proposed numerous modification methods to address ion transport and high-pressure interface stability issues in PEO. Regarding ion transport, methods such as introducing ionic liquids (CN114243088A), constructing three-dimensional ion transport frameworks (CN119725690A), and increasing lithium salt concentration (CN119162842A) can improve ionic conductivity by increasing the ion diffusion coefficient or carrier concentration. For high-pressure interface stability, introducing fluorinated additives (CN122224927A) or artificially constructing interface buffer layers (CN119208718A) can utilize interface passivation effects to suppress negative reactions. While these methods have achieved some success, they essentially rely on macroscopic methods to improve the apparent ion conduction and interface stability of the electrolyte, and the synergistic improvement effect is limited. They do not provide effective solutions to the root causes of PEO problems at the microscopic level.
[0004] Given the above difficulties, there is an urgent need to develop a modified PEO-based solid electrolyte that can significantly improve efficiency and solve the problems of ion conduction and interfacial stability of PEO from the root. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a modified PEO-based solid electrolyte, its preparation method and application. This invention uses organic additives with cation regulation function to significantly improve the ion conductivity and high-voltage interface stability of PEO-based solid electrolytes, and is suitable for long-life high-voltage all-solid-state lithium metal battery systems.
[0006] This invention provides the following technical solution: In one aspect, a modified PEO-based solid electrolyte is provided, comprising PEO, lithium salt, and organic additives; The organic additives include any one or more of lithium benzoate, lithium phthalate, lithium isophthalate, lithium terephthalate, and lithium 1,3,5-benzenetricarboxylate.
[0007] In the above technical solution, the organic additives used have an adsorption effect on lithium ions and hydrogen ions, which can weaken the strong binding effect of PEO on lithium ions and absorb hydrogen ions, thereby improving the ionic conductivity and high-voltage interface stability of PEO-based solid electrolytes.
[0008] Furthermore, the mass ratio of PEO, lithium salt and organic additive is 100:(10~100):(1~100).
[0009] Furthermore, the lithium salt includes any one or more of lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium dioxalateborate, and lithium difluorooxalateborate.
[0010] Furthermore, the particle size of the organic additive is 1 nm to 50 µm.
[0011] In a second aspect, a method for preparing the modified PEO-based solid electrolyte according to any one of the first aspects is provided, comprising: PEO and lithium salt are dissolved in an organic solvent and stirred thoroughly to obtain a PEO slurry; Organic additives are added to the polymer slurry and stirred thoroughly to obtain modified PEO slurry; The electrolyte slurry was cast onto a polytetrafluoroethylene plate, coated and vacuum dried to obtain a modified PEO-based solid electrolyte.
[0012] Furthermore, organic additives are added to the polymer slurry, stirred for 22-24 h, and ultrasonically dispersed for 2-4 h to obtain modified PEO slurry.
[0013] Furthermore, the height of the scraper in the coating process is 10~1000 µm, the temperature of the vacuum drying process is 30~80℃, and the vacuum drying time is 4~48 h.
[0014] Furthermore, the organic solvent includes any one or more of acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol dimethyl ether, tetrahydrofuran, or dimethyl sulfoxide.
[0015] Thirdly, the application of the modified PEO-based solid electrolyte described in any one of the first aspects in solid-state lithium batteries is provided.
[0016] Furthermore, the solid-state lithium battery includes a positive electrode, a negative electrode, and an electrolyte between the positive electrode and the negative electrode, wherein the electrolyte is a modified PEO-based solid-state electrolyte as described in any of the first aspects.
[0017] Furthermore, the positive electrode includes any one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, vanadium pentoxide, lithium-rich manganese-based oxide, lithium vanadate, or lithium titanate. The negative electrode includes any one of lithium metal or lithium alloy.
[0018] Furthermore, the thickness of the electrolyte is 1~300 μm.
[0019] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention addresses the root cause of the problems of ion transport and high-voltage interface stability of PEO-based solid electrolytes by using specific fillers to regulate the cation chemical environment. The carboxyl groups in the organic additives can weaken the strong binding effect of PEO on lithium ions and improve the ionic conductivity of PEO. At the same time, it absorbs the hydrogen protons generated by PEO under high voltage, preventing the strong acid environment from continuously damaging the electrode / electrolyte interface, and finally achieves a synergistic improvement in the ionic conductivity and high-voltage interface stability of PEO-based solid electrolytes. (2) The process for preparing modified PEO-based solid electrolytes in this invention is simple and efficient. The thickness of the prepared electrolyte is controllable and it has self-supporting properties, making it suitable for mass roll-to-roll processing and production. (3) The modified PEO-based solid electrolyte prepared by the present invention solves the problems of insufficient PEO ion conduction and high voltage interface stability in the high voltage lithium metal battery system. The assembled high voltage lithium metal battery has excellent discharge specific capacity and cycle stability. Attached Figure Description
[0020] Figure 1 This is a comparison of the ionic conductivity of the PEO-based solid electrolyte SS||SS symmetric cells of Example 3 and Comparative Example 1 at different temperatures. Figure 2 A linear sweep voltammetry comparison diagram of the Li||SS batteries with PEO-based solid electrolytes in Example 3 and Comparative Example 1 of the present invention. Figure 3 The electrochemical impedance spectroscopy of the PEO-based solid electrolyte in Example 3 and Comparative Example 1 before and after 10 cycles of 4.3 V Li||LMFP is shown in the graphs: (a) Example 1; (b) Example 3. Figure 4 This is a comparison chart of the rate performance of Li||LFP full cells with PEO-based solid electrolytes in Example 3 and Comparative Example 1 of the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention.
[0022] In the description of this invention, unless otherwise stated, "multiple" means two or more. The terms "comprising," "including," "having," "containing," etc., as used herein are open-ended, meaning they include but are not limited to.
[0023] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0024] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0025] Example 1
[0026] (1) Dissolve 800 mg of polyethylene oxide and 325.6 mg of lithium bis(trifluoromethanesulfonylimide) in 10 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) Add 200 mg of lithium benzoate to the PEO slurry, stir magnetically for 24 h, and ultrasonically disperse for 2 h to obtain the modified PEO slurry; (3) The modified PEO slurry was cast onto a polytetrafluoroethylene plate, coated with a 100 μm scraper, and vacuum dried at 40°C for 24 h to obtain a modified PEO-based solid electrolyte with a thickness of about 50 μm.
[0027] Example 2
[0028] (1) Dissolve 800 mg of polyethylene oxide and 325.6 mg of lithium bis(trifluoromethanesulfonylimide) in 10 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) 100 mg of lithium phthalate was added to the PEO slurry, magnetically stirred for 24 h, and ultrasonically dispersed for 2 h to obtain the modified PEO slurry; (3) The modified PEO slurry was cast onto a polytetrafluoroethylene plate, coated with a 200 μm scraper, and vacuum dried at 40°C for 24 h to obtain a modified PEO-based solid electrolyte with a thickness of about 100 μm.
[0029] Example 3
[0030] (1) Dissolve 200 mg of polyethylene oxide and 100 mg of lithium difluorosulfonyl imide in 10 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) Add 50 mg of lithium terephthalate to the PEO slurry, stir magnetically for 24 h, and ultrasonically disperse for 2 h to obtain the modified PEO slurry; (3) The modified PEO slurry was cast onto a polytetrafluoroethylene plate, coated with a 150 μm scraper, and vacuum dried at 40°C for 24 h to obtain a modified PEO-based solid electrolyte with a thickness of about 70 μm.
[0031] Example 4
[0032] (1) Dissolve 200 mg of polyethylene oxide and 81.4 mg of lithium bis(trifluoromethanesulfonylimide) in 10 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) 20 mg of lithium isophthalate and 20 mg of lithium 1,3,5-tribenzoate were added to the PEO slurry, magnetically stirred for 24 h, and ultrasonically dispersed for 2 h to obtain the modified PEO slurry; (3) The modified PEO slurry was cast onto a polytetrafluoroethylene plate, coated with a 150 μm scraper, and vacuum dried at 40°C for 24 h to obtain a modified PEO-based solid electrolyte with a thickness of about 70 μm.
[0033] Comparative Example 1 (1) Dissolve 800 mg of polyethylene oxide and 325.6 mg of lithium bis(trifluoromethanesulfonylimide) in 12 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) PEO slurry was poured onto a polytetrafluoroethylene plate, coated with a 100 μm scraper, and vacuum dried at 40°C for 24 h to obtain a PEO-based solid electrolyte with a thickness of about 50 μm.
[0034] Comparative Example 2 (1) Dissolve 200 mg of polyethylene oxide and 81.4 mg of lithium bis(trifluoromethanesulfonylimide) in 10 ml of acetonitrile and stir magnetically until completely dissolved to obtain PEO slurry; (2) PEO slurry was poured onto a polytetrafluoroethylene plate, coated with a 150 μm scraper, and vacuum dried at 40°C for 24 h to obtain a PEO-based solid electrolyte with a thickness of about 70 μm.
[0035] Application Example 1 The modified PEO-based solid electrolytes prepared in Examples 1-4 were assembled with two stainless steel discs (SS) to form SS||SS coin cells. AC impedance spectroscopy was performed at 60°C using a CHI660E electrochemical workstation from Shanghai Chenhua, with the test frequency band being 10 GHz. 6 With a Hz frequency of ~0.1 Hz and an AC voltage of 10 mV, the ionic conductivity of the solid electrolyte was calculated using impedance spectroscopy information, and the results are shown in Table 1.
[0036] Table 1. Ionic conductivity test results of different PEO-based solid electrolytes at 60℃
[0037] As can be seen from Table 1, the ionic conductivity of the modified PEO-based solid electrolytes prepared in Examples 1-4 is higher than that of the PEO-based solid electrolytes prepared in Comparative Examples 1-2, indicating that the organic additives with cation regulation function can weaken the binding effect of PEO on lithium ions and significantly improve the ion transport of PEO.
[0038] The PEO-based solid electrolytes prepared in Examples 1-4 and Comparative Examples 1-2 were assembled with lithium metal anode (Li) and lithium manganese iron phosphate cathode (LMFP) to form Li||LMFP coin cells. The long-cycle performance of the Li||LMFP full cells was tested at 60°C using the CT-4008T battery testing system of Shenzhen Xinwei, with a voltage range of 2.5-4.3 V and a test rate of 0.5 C. The results are shown in Table 2.
[0039] Table 2. Long-cycle performance test results of Li||LMFP full cells with different PEO-based solid electrolytes
[0040] As can be seen from Table 2, compared with the test results of Comparative Examples 1-2, the Li||LMFP full cells prepared by the modified PEO-based solid electrolyte in Examples 1-4 exhibit higher discharge specific capacity and capacity retention rate. This indicates that the organic additive with cation regulation function can synergistically enhance the ionic conductivity and high-voltage interface stability of the PEO-based solid electrolyte, and has better cycle performance in the 4.3 V high-voltage lithium metal battery system.
[0041] Application Example 2 As can be seen from the results of Application Example 1, the performance of Example 3 is better than that of other samples. This application example selects the samples of Example 3 and Comparative Example 1 to further explore the effect of organic additives with cation regulation function on the performance of PEO-based lithium metal batteries.
[0042] Figure 1 A comparison of the ionic conductivity of SS||SS symmetric cells assembled with two PEO-based solid electrolytes at different temperatures is shown in the graph. The test conditions are consistent with those provided in Application Example 1, with a temperature range of 30–80 °C. Figure 1 As can be seen, compared with Comparative Example 1, the modified PEO-based solid electrolyte prepared in Example 3 has a higher ionic conductivity, proving that organic additives with cation regulation function can weaken the binding effect of PEO on lithium ions and significantly improve the ionic conductivity of PEO.
[0043] Figure 2 To analyze the oxidation potential of Li||SS cells assembled with two PEO-based solid electrolytes using linear sweep voltammetry, the voltage range was 0–6 V, and the scan rate was 1 mV / s. Figure 2 As can be seen, compared with Comparative Example 1, the modified PEO-based solid electrolyte prepared in Example 3 has significantly improved oxidation stability, with the oxidation potential increasing to 5.1 V, indicating that organic additives with cation regulation function can significantly improve the high-pressure stability of PEO.
[0044] Figure 3 The graphs show the electrochemical impedance spectroscopy of Li||LMFP batteries assembled with two PEO-based solid electrolytes before and after 10 cycles, with test conditions consistent with those provided in Application Example 1. Figure 3 It can be seen that the interfacial impedance of the PEO-based solid electrolyte prepared in Comparative Example 1 increased significantly after cycling, while the interfacial impedance of the modified PEO-based solid electrolyte prepared in Example 3 remained almost unchanged after cycling. This indicates that the organic additive with cation regulation function can effectively absorb the hydrogen ions generated by the decomposition of PEO at 4.3 V high pressure, and prevent the increase in interfacial impedance caused by the corrosion of the interface in a strongly acidic environment.
[0045] Figure 4 The graph shows the rate performance of a Li||LFP coin cell symmetric battery assembled with two electrolytes, with the rate test range being 0.1~3C and the voltage range being 2.5~4V. From... Figure 4 As can be seen, the Li||LFP full cell assembled with the modified PEO-based solid electrolyte prepared in Example 1 exhibits superior rate performance, maintaining a high discharge specific capacity of 136.1 mAh / g at a 3 C rate, demonstrating the fast ion conduction capability and interface stability of the modified PEO-based solid electrolyte.
[0046] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A modified PEO-based solid electrolyte, characterized in that, Including PEO, lithium salts, and organic additives; The organic additives include any one or more of lithium benzoate, lithium phthalate, lithium isophthalate, lithium terephthalate, and lithium 1,3,5-benzenetricarboxylate.
2. The modified PEO-based solid electrolyte according to claim 1, characterized in that, The mass ratio of PEO, lithium salt and organic additive is 100:(10~100):(1~100).
3. The modified PEO-based solid electrolyte according to claim 1, characterized in that, The lithium salt includes any one or more of lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium dioxalateborate, and lithium difluorooxalateborate.
4. The modified PEO-based solid electrolyte according to claim 1, characterized in that, The particle size of the organic additive is 1 nm to 50 µm.
5. A method for preparing the modified PEO-based solid electrolyte according to any one of claims 1 to 4, characterized in that, include: PEO and lithium salt are dissolved in an organic solvent and stirred thoroughly to obtain a PEO slurry; Organic additives are added to the polymer slurry and stirred thoroughly to obtain modified PEO slurry; The electrolyte slurry was cast onto a polytetrafluoroethylene plate, coated and vacuum dried to obtain a modified PEO-based solid electrolyte.
6. The method for preparing the modified PEO-based solid electrolyte according to claim 5, characterized in that, Organic additives were added to the polymer slurry, stirred for 22-24 h, and ultrasonically dispersed for 2-4 h to obtain the modified PEO slurry. And / or, the height of the scraper in the scraping process is 10~1000 µm, the temperature of the vacuum drying is 30~80℃, and the vacuum drying time is 4~48 h; And / or, the organic solvent includes any one or more of acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol dimethyl ether, tetrahydrofuran, or dimethyl sulfoxide.
7. The application of the modified PEO-based solid electrolyte according to any one of claims 1 to 4 in solid-state lithium batteries.
8. The application according to claim 7, characterized in that, The solid-state lithium battery includes a positive electrode, a negative electrode, and an electrolyte between the positive electrode and the negative electrode, wherein the electrolyte is the modified PEO-based solid electrolyte as described in any one of claims 1 to 4.
9. The application according to claim 8, characterized in that, The positive electrode includes any one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, vanadium pentoxide, lithium-rich manganese-based oxide, lithium vanadate, or lithium titanate. The negative electrode includes any one of lithium metal or lithium alloy.
10. The application according to claim 8, characterized in that, The thickness of the electrolyte is 1~300 μm.
Citation Information
Patent Citations
PEO-based composite solid electrolyte as well as preparation method and application thereof
CN114243088A
Light ultrathin PEO-based solid electrolyte with high ion transfer number and preparation method thereof
CN119162842A
Method for modifying solid electrolyte-high-voltage positive electrode interface through double-filler doped interface buffer layer
CN119208718A
Composite solid electrolyte membrane and preparation method and application thereof
CN119725690A
Fluorine-sulfur synergistically modified PEO-based composite solid electrolyte and preparation method thereof
CN122224927A